2015
DOI: 10.4314/njt.v34i3.25
|View full text |Cite
|
Sign up to set email alerts
|

Radio Refractivity Study in Akure-Owo Digital Microwave Link in South Western Nigeria

Abstract: This work is a study of radio refractivity in Akure This work is a study of radio refractivity in Akure This work is a study of radio refractivity in Akure This work is a study of radio refractivity in Akure-Owo Digital Microwave Link in South Western Nigeria. Owo Digital Microwave Link in South Western Nigeria. Owo Digital Microwave Link in South Western Nigeria. Owo Digital Microwave Link in South Western Nigeria. Meteorological data of air temperature, atmospheric pressure, relative humidity, and water vapo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…The troposphere, also called the lower atmosphere is the area of the atmosphere that reaches heights of 8 to 10 kilometers at arctic latitudes, 10 to 12 kilometers at mild latitudes, and 16 to 18 kilometers at the equator [2]. It is in the layer of the atmosphere that the majority of the meteorological events happen, such as rain, hurricanes, lightning, cyclones, snows, and fronts [3]. In the troposphere, the percentage of the gas components does not vary with height.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The troposphere, also called the lower atmosphere is the area of the atmosphere that reaches heights of 8 to 10 kilometers at arctic latitudes, 10 to 12 kilometers at mild latitudes, and 16 to 18 kilometers at the equator [2]. It is in the layer of the atmosphere that the majority of the meteorological events happen, such as rain, hurricanes, lightning, cyclones, snows, and fronts [3]. In the troposphere, the percentage of the gas components does not vary with height.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers in Nigeria, such as [1], [3], [13], [15]- [22] have worked on the effect of atmospheric factors on radio propagation, but latitudinal variations of some specific locations considered in this work have not been dealt with extensively considering the two major seasons usually experience in Nigeria.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore evaluating temperature variation is important in predicting radio signal propagation [3]. It is widely agreed that variations in pressure, temperature and relative humility within the troposphere causes changes in the refractive index of air which can affect the propagation of signals [4]. There are several researches on the variation of radio refractivity in Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…There are several researches on the variation of radio refractivity in Nigeria. [4] Investigated the radio refractivity in Akure, south west Nigeria and concluded that the refractivity gradient was greater than zero and vary slightly throughout the months of the year. [2] Studied surface radio refractivity in Akwa, south eastern Nigeria.…”
Section: Introductionmentioning
confidence: 99%